Conservative surgical management of a ruptured non-communicating rudimentary horn of pregnancy at 13 weeks period of gestation in previous caesarean delivery - A Rare Case Report - T Sai Tejaswi; Rajasri Yaliwal; S R Mudanur; Aruna Biradar; Shreedevi Kori; Shivakumar Pujeri (Wolters Kluwer Medknow Publications, 2020)
Introduction: Unicornuate uterus with Non- communicating rudimentary horn occurs due to failure of complete development of one of the Mullerian ducts and incomplete fusion with the contralateral side. Pre rupture diagnosis of pregnancy in rudimentary horn with ultrasonography is technically difficult and missed frequently (sensitivity 30%). Many times it is diagnosed during laparotomy. The standard treatment is excision of the ruptured horn. However, this is technically difficult due to distorted anatomy, time-consuming and can lead to more blood loss. In this case, the ruptured horn was repaired and the surgery was coupled with bilateral tubectomy. This is a new conservative approach to rupture the non-communicating horn of pregnancy. Case Report: A 27-year-old woman presented to us with a history of amenorrhea of 13 weeks and abdominal pain. Her obstetric score was Gravida 3 Para 2 Living 2. She had undergone 2 cesarean sections which were uneventful. On ultrasonography, the gestational sac was seen outside the uterus, hence a diagnosis of ruptured ectopic was made. As she was hemodynamically unstable and she had completed her family and consented for tubectomy, a decision to repair the horn was made. Conclusion: Diagnosis and management of rudimentary horn pregnancy remain a challenge. A high index of suspicion during a prenatal ultrasound can result in early diagnosis, and thereby resulting in decreased maternal morbidity and mortality. A Conservative surgical approach coupled with tubectomy in women who have completed their families can decrease operative time, blood loss and potential complications due to distorted anatomy.